2023
DOI: 10.2174/1566524022666220509124608
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis and Cancer Immunotherapy

Abstract: Traditional treatment strategies of cancer are far from satisfaction. As a non-apoptotic cell death process and owning to the characteristics of iron-dependent lipid peroxide accumulation, ferroptosis has become a new target of tumor treatment. Numerous studies have proved that ferroptosis could enhance the immunogenicity of cancer and interact with immune cells. Cancer antigens, exposed to cancer cells underwent ferroptosis, effectively improve the immunogenicity of the tumor microenvironment and promote the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…SLC3A2 is a key chaperone for xCT in the process of ferroptosis, metabolism and proliferation in cancer cells [31][32][33]. Owing to these diverse molecular functions, overexpression of SLC3A2 has been found associated with the development and progression of various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…SLC3A2 is a key chaperone for xCT in the process of ferroptosis, metabolism and proliferation in cancer cells [31][32][33]. Owing to these diverse molecular functions, overexpression of SLC3A2 has been found associated with the development and progression of various types of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that multiple factors are involved and controlled in tumorigenesis. Sustained growth signaling, unlimited replication potential, antiapoptotic factors, acquisition of invasive metastasis, reprogramming of cell metabolism, and TME are major hallmarks of cancer malignancy ( Hanahan and Weinberg, 2011 ; Wong, 2011 ; Mossmann et al, 2018 ; Xiao and Yu, 2021 ; Yin et al, 2022 ). However, tumors exhibit extreme heterogeneity, which is characterized by mutations in genes and alterations in the TME ( Paul et al, 2019 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ferroptosis is an immunogenic cell death. This additional tumor suppression mechanism could be successfully exploited in immunotherapy [ 20 ]. For example, nanoparticles charged with RSL-3 not only initiated T lymphocyte activation and antitumoral response but also increased resistance to lipid damage repair in tumor cells, leading to accumulation of ROS [ 73 ] and sensitivity to radiotherapy [ 74 ].…”
Section: Ferroptosis and Immunitymentioning
confidence: 99%
“…Thus, ferroptosis can be used to eliminate tumor cell subpopulations responsible for cancer recurrence. To increase the anticancer effect, ferroptosis can be coupled with chemotherapy [ 17 ], radiation therapy [ 18 ], photodynamic therapy [ 19 ], and, being an immunogenic cell death, with immunotherapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%